(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study analyzes exponentially accelerating fluid through vertically porous plate with a heat source. The effects of rotation, porosity, and Thermal Radiation on velocity (Speed), temperature (Warmth), and concentration(accumulation) profiles are investigated. Results indicate that velocity rises with heat source increase but decreases with radiation and rotation. Temperature increases with heat generation raises while concentration drops with higher Schmidt numbers. Also, Skin friction, Nusselt & Sherwood values tabulated.